Critiques of Appropriation and Transnational Labor Ethics. (7th June 2022) - Delice, Serkan
Abstract: Ideas and concepts have their own lives and resilience, to which one should be sensitive. This article focuses on the ways in which a group of Indian artisan organizations and collectives deploy—in their critical exchange with a designer and retailer that have privileged access to the transnationally circulating capital—the concept of appropriation as a tool to confront the hierarchical divisions of labor, and the unequal distribution of capital, within the globalized circuits of transnational fashion production. In bringing together Karl Marx's critique of the appropriation of living labor by objectified labor and David Harvey's critical exposé of the new mechanisms of "accumulation by dispossession, " and connecting these labor-focused perspectives on appropriation to the phenomenon of so-called cultural appropriation, the following investigates the potentiality of appropriation in facilitating a transnational labor ethics that defies the problematic segregation of the "design" and "creative" processes from the increasingly alienated and absorbed productive forces of the dispossessed artisan and craft communities.